1987
DOI: 10.1021/jm00387a018
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene receptor antagonists. 1. Synthesis and structure-activity relationships of alkoxyacetophenone derivatives

Abstract: A series of derivatives of 2,4-dihydroxy-3-propylacetophenone(1) were prepared and examined for their ability to block leukotriene D4 (LTD4) induced contraction of guinea pig ileum. Straight-chain carboxylic acids where the carboxyl group was separated from the acetophenone moiety by varying numbers of methylenes were evaluated, and maximum activity was obtained with the pentamethylene acid (6). Examination of ring substitution showed that the 2-propyl-3-hydroxy-4-acetyl substitution pattern was required for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Various examples from the literature show that the pharmacodynamic effect can increase, decrease, or completely disappear. [24] Through the substitution of a carboxylic acid by a 5-ST, its in vitro activity was increased by approximately thirty times, probably due to a better interaction between the delocalized negative charge on the tetrazole ring and the arginine residue in the active site of the cysLT 1 receptor for LTD 4 . One of the first in vivo studies found that the tetrazole analogue of nicotinic acid was excreted unchanged, whereas nicotinic acid itself was quickly metabolized.…”
Section: -Sts In Medicinal Chemistrymentioning
confidence: 99%
“…Various examples from the literature show that the pharmacodynamic effect can increase, decrease, or completely disappear. [24] Through the substitution of a carboxylic acid by a 5-ST, its in vitro activity was increased by approximately thirty times, probably due to a better interaction between the delocalized negative charge on the tetrazole ring and the arginine residue in the active site of the cysLT 1 receptor for LTD 4 . One of the first in vivo studies found that the tetrazole analogue of nicotinic acid was excreted unchanged, whereas nicotinic acid itself was quickly metabolized.…”
Section: -Sts In Medicinal Chemistrymentioning
confidence: 99%
“…We speculate through the investigation of a series of chemically modified compounds with similar structure (not shown) and from other reports (Feuer, 1977;1981;Dhai, 1979) that the serum ALT lowering effect is due to the thiadiazol structure at 3-methyl position of the YM-16638 molecule; however, we still have insufficient data to confirm this point. LY-171883 (Eli Lilly Co., Ltd., U.S.A.), a potent and leukotriene antagonist with a similar structure to YM-16638, (Marshall et al, 1987;Fleisch et al, 1985) is known to decrease serum triglyceride level in rats and monkeys, but not serum cholesterol level and ALT activity (Eacho et al, 1985;Foxworthy et al, 1990;Hoover et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…During the past 15 years several potent and selective CysLT 1 antagonists have been developed (Scheme 1). 14 At first the development of new CysLT 1 antagonist was mainly inspired by FPL 55712 22 or LTD 4 analogues, e.g. probilukast (SK&F 104353).…”
Section: Introductionmentioning
confidence: 99%